2000
DOI: 10.2214/ajr.175.6.1751677
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Alcoholic from Virus-Induced Cirrhosis on MR Imaging

Abstract: Enlargement of the caudate lobe and the presence of the right posterior hepatic notch on MR imaging are more frequent findings of alcoholic cirrhosis than of virus-induced cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 24 publications
2
42
1
1
Order By: Relevance
“…The distinct hypertrophy of the caudate lobe in alcoholic cirrhosis is the same as that noted in a previous study. 15 In patients with NASH classified as patients with Child-Pugh Class A, these morphometric changes other than hypertrophy of the caudate lobe progressed less than in those with virus-related and alcoholic cirrhosis. The hypertrophy of the caudate lobe progressed more than in patients with virus-related cirrhosis, as well as in patients with alcoholic cirrhosis.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The distinct hypertrophy of the caudate lobe in alcoholic cirrhosis is the same as that noted in a previous study. 15 In patients with NASH classified as patients with Child-Pugh Class A, these morphometric changes other than hypertrophy of the caudate lobe progressed less than in those with virus-related and alcoholic cirrhosis. The hypertrophy of the caudate lobe progressed more than in patients with virus-related cirrhosis, as well as in patients with alcoholic cirrhosis.…”
Section: Discussionmentioning
confidence: 96%
“…6,7,10,15 We for the first time revealed that NASH-related cirrhosis showed the same patterns of The proportion of lateral segment to the total liver was significantly smaller in patients with non-alcoholic steatohepatitis (NASH) than in those with alcoholic cirrhosis (p , 0.001), the proportion of the medial segment was significantly larger in patients with NASH than in those with alcoholic cirrhosis (p 5 0.045), the proportion of the anterior segment was significantly larger in the patients with NASH than in those with alcoholic cirrhosis (p 5 0.003) and the proportion of the caudate lobe was significantly smaller in the patients with virus-related cirrhosis than in those with alcoholic liver cirrhosis (p 5 0.001). There were no significant differences in the proportion of the posterior segment and right lobe to the total liver among the patients with the three different aetiologies (p .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O encontro destas alterações pela RM corrobora as alterações descritas vistas na US . É interessante notar, no entanto, que outras afecções podem, eventualmente, cursar com essas alterações, mais notadamente a cirrose, seja ela de etiologia alcoó-lica ou viral (43,50) . A fibrose periportal já foi considerada patognomônica de esquistossomose e a sua caracterização é importante para a avaliação do estádio da doença, bem como para acompanhar o sucesso do tratamento (35,(53)(54)(55) .…”
Section: Discussionunclassified
“…On MRI, specific features suggestive for alcoholic cirrhosis versus virus-induced cirrhosis include a higher volume index of the caudate lobe, smaller size of regenerative nodules of the liver and more frequent visualization of the right posterior hepatic notch [6] . On US liver scan, the presence of "pseudoparallel channel signs" and of low hepatic artery resistivity index (RI) at duplex Doppler investigation have both been reported in AAH [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%